Pengaruh Latihan Dumbell Terhadap Peningkatan Daya Ledak Otot Lengan Pada Pemain Bulu Tangkis Di Gor Pabelan Surakarta - Misbahunnur, Muh (2017)
Muscle explosive power is one of the physical components required in a variety of sports, especially badminton. Many novice badminton players have weakness when it hit the shuttlecock resulting from the lack of explosive power arm muscles. Exercise can increase the explosive power of muscles in your arms one of which is an exercise dumbbell.To determine the effect of exercise to increase explosive power dumbell bicep on a badminton player in GOR Pabelan using a measuring instrument Two Hand Medicine Ball Put. This type of research is pre experiment with pre test - post test one group design. The number of samples in this study amounted to 20 peoples. The results showed Award workout dumbell with 12x exercise for 4 weeks with 8 reps, 6 sets of each exercise can increase the explosive power of the arm muscles in badminton players, from a mean value of pre test is 2.735 meters, up to a mean value of post test is 3,630 meters with a difference the mean pre and post amounted to 0.895 meters. While the results of the analysis of the results obtained using the Wilcoxon test, p = 0.000 <0.05, which means that there is influence Dumbbell Exercises To Improve Muscle Burst Arm In Cast Badminton Starter In GOR Pabelan Surakarta.there is influence Dumbbell Exercises To Improve Muscle Burst Arm In Cast Badminton Starter In GOR Pabelan Surakarta. Keywords: Dumbell exercise, exsplosive muscle power arm, Two Hand Medicine Ball Put, badminton players.